Obserwacja i trwanie – O liryczności wierszy ks. Janusza St. Pasierba - Bałdyga, Katarzyna (Colloquia Litteraria, 2014)
Observation and endurance: on lyricism in Fr. Janusz St. Pasierb’s poems Limiting Fr. Janusz Stanisław Pasierb’s poetry exclusively to references to the Bible and the salvation history restricts understanding of the phenomenon of his poetry. Noticing the dialogicality of the speaking subject allows for grasping the most relevant in his poetry – experience accessible to the senses is moved to a higher level. The poet accurately and with minute precision notes down what is available to the senses; also, being aware of entanglement in time and space of human experience, he incorporates into his poetry a small surplus – he rips the experience from the horizontally oriented world and immerses it in transcendent reality. Observation and endurance are pillars of thinking about lyricism; Pasierb’s poems show how the prospect of eternity consolidates the value of a single experience.